Demethylcalabaxanthone from Garcinia mangostana Exerts Antioxidant Effects through the Activation of the Nrf2 Pathway as Assessed via Molecular Docking and Biological Evaluation - Simona De Vita; Milena Masullo; Sabrina Grambone; Paloma Bermejo Bescós; Sonia Piacente; Giuseppe Bifulco (MDPI AG, 2023)
Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway activation promotes the expression of antioxidant enzymes in response to rising oxidative stress, resulting in reactive oxygen species (ROS) detoxification and playing a central role in the maintenance of intracellular redox homeostasis and regulation of inflammation. Moreover, the biological effects of Nrf2 pathway activation contribute to reducing apoptosis and enhancing cell survival. The activity of Nrf2 is negatively regulated by Kelch-like ECH-associated protein 1 (Keap1). Prompted by the recent results reporting the impact of xanthone metabolites on oxidative stress, cancer, and inflammation, the antioxidant properties of xanthones isolated from Garcinia mangostana (γ-mangostin, α-mangostin, 8-deoxygartanin, demethylcalabaxanthone, garcinone D) were assessed. In particular, the capability of these natural products to disrupt the interaction between Kelch-like ECH-associated protein 1 (Keap1) and nuclear factor erythroid 2-related factor 2 (Nrf2), triggering the activation of the Nrf2-mediated pathway, was evaluated using molecular docking experiments and in vitro tests. The modulation of some key Nrf2-related mediators like glutathione (GSH) and lactate dehydrogenase (LDH) to highlight a possible direct antioxidant effect was investigated. Among the tested compounds, demethylcalabaxanthone showed an indirect antioxidant effect, as corroborated by a Western blot assay, displaying a significant increase in the translocated protein upon its administration.